Net Zero climate commitments : realistic goal or branding exercise? - Isaacs, Andrew, (SAGE business cases., 2023)
In 2022, companies of all sizes and across multiple industries started to create and publicly announce Net Zero climate commitments. At the time, there was no generally accepted definition of "Net Zero" and instead, each company defined what metrics were included in tracking their commitment. Further, there was no globally recognized third-party accountability mechanism that would assure that these promises were being fulfilled; leaving companies to report their own progress without outside, independent verification. As a result, many questions around the validity of these claims and their true impact on climate change were left unanswered. For example: How serious and achievable were these Net Zero claims? Behind these claims, how much effort was focused on customer appeal versus a core business strategy? How realistic were these claims and was there a plan by the company to back them up? With so many claims, how do stakeholders distinguish the true Net Zero commitments from those that are simply making the claim for the sake of the company brand?